Living arrangements of the elderly and the sociodemographic and health determinants: a longitudinal study - Alisson Fernandes Bolina; Darlene Mara dos Santos Tavares
ABSTRACT Objectives: to describe the sociodemographic characteristics and the number of morbidities in the elderly, according to the dynamics of living arrangements and evaluate the sociodemographic and health determinants of the living arrangements. Methods: this is a household longitudinal survey (2005-2012), carried out with 623 elderly people. Descriptive statistical analysis and multinomial logistic regression were performed (p<0.05). Results: there was predominance of elderly living alone, accompanied and with change in the living arrangements, females, age range between 60├ 70 years, 1├ 4 years of study and with income between 1├┤ 3 minimum wages. During the development of this research, it was identified an increase in the incidence of elderly with 1├┤3 minimum wages. The number of morbidities increased in the three groups throughout the study, with the highest rates observed among the elderly with change in the dynamics of living arrangements. It was found that elderly men showed less chance of living alone (p=0.007) and having change in the living arrangements compared to women (p = 0.005). Incomes less than a minimum wage decreased the chances of change in the living arrangements compared to incomes above three salaries (p=0.034). Conclusion: the determining factors of the living arrangements were sex and income, and the variables functional capacity and number of morbidities were not associated with the outcome analyzed.